2015
DOI: 10.4103/0259-1162.156347
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different types of pharyngeal packing in patients undergoing nasal surgery: A comparative study

Abstract: Context:Postoperative throat complaints such as postoperative sore throat (POST), dysphagia, and hoarseness frequently arises after tracheal intubation and throat packing for patient undergoing general anesthesia. This condition is very disturbing to patient. Avoiding POST is a major priority for these patients because preventing postoperative complications contributes to patient satisfaction.Aims:To describe and analyze the postoperative throat effects of nasopharyngeal packing and oropharyngeal packing in pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Eleven studies, with 931 participants, were reviewed for eventual inclusion in this meta-analysis [1][2][3][4][5][6][7][8][9][10][11]. The study characteristics and quality assessment are presented in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Eleven studies, with 931 participants, were reviewed for eventual inclusion in this meta-analysis [1][2][3][4][5][6][7][8][9][10][11]. The study characteristics and quality assessment are presented in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…-Low methodological quality, with a modified Jadad score of less than 4 (n = 4) [10,[29][30][31]. -Ongoing study with results not yet published (n = 8) [32][33][34][35][36][37][38][39].…”
Section: Selection Of Studiesmentioning
confidence: 99%
“…Posterior throat packs are often-used in rhinology surgery to help in protecting the airway against aspiration and in the reduction of ponv 5 . However, many studies concluded that posterior throat packs are associated with higher amounts of post-operative pain, nausea 2,6,7 , vomiting, and in some rare cases even forgotten in the patient leading to mortality 8 . Despite poor evidence in the literature, the placement of posterior throat packs is commonly practiced by surgeons and anesthetists because the possible risk of aspiration is worrisome 9 .…”
Section: Introductionmentioning
confidence: 99%